NEW DATA ON THE CONDITIONS OF SEDIMENTATION OF UPPER JURASSIC CARBONATE COMPLEX IN THE TERRITORY OF PREDOBROGEAN FOREDEEP - Zhabina, N.; Anikeyeva, O.; Samarska, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The results of complex micropaleontological and microfacial studying of Upper Jurassic sediments of Predobrogean regions of Ukraine are produced. According to nowadays stratigraphy scheme, in the Predobrogean foredeep the Upper Jurassic is represented by carbonate complex in which there are reefogenic facies of Middle Oxfordian–Lower Kimmeridgian, and terrigenous lagoonal-continental formations of Upper Kimmeridgian–Tithonian. The investigations allowed to reveal planktonic microfauna – tintinnids in the Oxfordian and Tithonian, to make characteristic of microfacial composition of the rocks. The result are the determinztion of presence of pelagic possibly fore-reef sediments of the Upper Tithonian and back-reef formations of Kimmeridgian, Tithonian and Tithonian–Berriassian. This gave the base for the new interpretation of age, facies and conditions of forming Upper Jurassic sediments of the Predobrogean foredeep. The following facies were determined in the Upper Jurassic complex: fore-reef, reef and back-reef in the Oxfordian, back-reef and lagoonal in the Kimmeridgian, fore-reef, back-reef and lagoonal in the Tithonian. Analysis of the vertical sequences in the sections studied allowed to clear the conditions of forming the Upper Jurassic sediments of Predobrogean foredeep and their alternations in time because of transgressive-regressive processes. In Oxfordian the sediments were formed on the rather shallow shelf: in the south – a deeper-water pelagic, in the northeast – shallow-water back-reef, and reef zone as arc stretched from northwest to southeast. Long regressive background caused the vertical zonation of the Oxfordian reefs in the region. Pelagic sediments of Oxfordian were overlapped by shallow-water formations and evaporitic lagoon began forming on the most territory. As a result of global transgression in Tithonian the sea spreaded in the south and center of the foredeep. The lagoon continued to exist on the raised periphery of the basin. Upper Jurassic carbonate complex was considerably eroded afterwards and was partly overlapped by nappe structures. This completed reefogenic complex which is absent here.